2016
DOI: 10.5812/jjm.35237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Mucor and Lichtheimia Species in Pure Cultures of Zygomycetes

Abstract: BackgroundThe Mucorales are an important opportunistic fungi that can cause mucormycosis in immunocompromised patients. The fast and precise diagnosis of mucormycosis is very important because, if the diagnosis is not made early enough, dissemination often occurs. It is now well established that molecular methods such as polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) are feasible and reliable tools for the early and accurate diagnosis of mucormycosis agents.ObjectivesThe present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Unlike bacteria, the identification and organization of fungi still rely mostly on morphological features and the use of light microscope relics to be dynamic in fungiform investigations. However, such identification techniques may be problematic and time-consuming as they may need specific proficiency to obtain consistent evidence (Ziaee et al, 2016). In the current research, both macroscopic features and microscopic practices were used to identify fungal isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike bacteria, the identification and organization of fungi still rely mostly on morphological features and the use of light microscope relics to be dynamic in fungiform investigations. However, such identification techniques may be problematic and time-consuming as they may need specific proficiency to obtain consistent evidence (Ziaee et al, 2016). In the current research, both macroscopic features and microscopic practices were used to identify fungal isolate.…”
Section: Discussionmentioning
confidence: 99%
“…New strains in this study were with 98% identity with L. corymbifera. In Ziaee et al's study, 9.17% of 120 pure Mucorale cultures belonged to L. corymbifera (20). Absidia corymbifera is the pathogenic species of the genus Absidia reclassified as L. corymbifera (21,22).…”
Section: Discussionmentioning
confidence: 96%
“…It is reported that among the 78% patients discovered of mucormycosis infection by the histopathology or smear test, only 55% are cultureanalysis positive [6]. The morphological characteristic of mucormycosis is specific with thick hyphae (5~15 nm in diameter) and irregular but rarely separated branch, which is just the opposite of Aspergillus [16,17]. In other ways, PCR method is currently a hot topic in molecular diagnosis of mucormycosis and a large amount of reports have pointed out that primer probes designed specifically to the fungal ITS, 28S or other region can contribute to the detection of different fungal types.…”
Section: Discussionmentioning
confidence: 99%
“…He was cured through combination of amphotericin B therapy and surgical treatment, indicating that surgical operation is of great significance for the recovery of local mucormycosis infection. Many factors including immune function and the patient's age have important effect on the outcome for mucormycosis infection and the prognosis of children is better compared withthe elder [17,23].…”
Section: Discussionmentioning
confidence: 99%